The bet to achieve quality in banking information systems using internal marketing strategies in the National Bank of Algeria - hadjab, moussa; Mezghiche , Abd alhalim (Journal of Research in Finance and Accounting, 2022)
This research aims to determine the extent to which internal marketing strategies are adopted in Algerian banking institutions as a mechanism of modern management, the extent to which it reflects on the activation and improvement of their information systems quality, and its implications for the performance and competitiveness of Algerian banks. The research addresses the most important concepts and elements of the administrative systems and examines the case of one of the most important Algerian banks, the National Bank of Algeria, through a statistical exploratory study depends on a questionnaire directed to the frames of three central agencies: Reghaia, Rouiba, and Boumerdes agencies, leading to identify the relationship between study variables and the testing of their hypotheses.